The Birth of the “Indian” Clinic: Daktari Medicine in A Ballad of Remittent Fever - Thiyagaraj Gurunathan; Binod Mishra (Humanities)
This article locates the clinic as a historically contingent space which faced cultural resistance and remained alien to the colonized population in India. It corroborates the socio-political tension in setting up a clinic within the colony and investigates how the Western clinic as a colonial apparatus was resituated as the “Indian clinic” per se. With the historical emergence of a new class of medical practitioners called “daktars” (a Bengali vernacularization of the term “doctor”), the health-seeking behaviour and public health model of colonial India witnessed a decolonial shift. Unlike their English counterparts, daktars did not enjoy a privileged position within the medical archives of colonial India. This archival gap within Indian medical history presents itself as a viable topic for discussion through the means of the literature of the colonized. Bengali writer Ashoke Mukhopadhyay’s novel Abiram Jwarer Roopkotha (2018), translated into English as A Ballad of Remittent Fever in 2020, remedies the colonial politics of the archive by reconstructing the lives of various daktars and their pursuit of self-reliance. The article takes a neo-historical approach towards understanding and assessing the past of daktari medicine and thereby offers comments on its traces in the contemporary public health of India.